Shareholders loans: a simple method of money laundering - Alves, Jorge (2018)
This study aims to discuss money laundering from a new perspective. For Mitchell et al. (1998) and Bingham (1992), among others, underlying money laundering there are complex webs of transactions with the purpose of “cleaning” illicit funds, transmitting them “through the banking system in such a way as to disguise the origin or ownership of the funds”. One reads this description and thinks of dark environments, gangsters and drug dealers. However, money can be laundered in simple ways that the literature does not discuss, and are familiar for many people. It is the case of shareholders loans that can be used as a solution for cleaning the proceedings of invoiceless sales firms make. For the Portuguese case, we gather empirical evidence and test the hypothesis that such loans are used as a laundry solution for those proceedings. We use a methodology based on two main steps. First, it classifies firms according to their tax fraud behavior by invoiceless sales; second, it relates shareholders loans to such proceedings. We found a positive relationship between these two variables. This result will be a contribution to the literature bringing into the discussion another money laundry tool.